Impact of the COVID-19 pandemic on the epidemiological and clinicopathological profile of cases of primary cutaneous melanoma diagnosed at Professor Rubem David Azulay Institute of Dermatology - Elena de Lima Madureira; Dina Zylbersztejn; Alice Mota Buçard; David Rubem Azulay (Sociedade Brasileira de Dermatologia (SBD), 2023)
SUMMARY: Melanoma is the main cause of death in dermatology (it is an aggressive type of skin cancer being one of the main causes of cancer death) due to its high metastatic power. When detected in early stages, its surgical treatment can be curative. When detected in more advanced stages, its prognosis is reserved and can be lethal. During the period of the COVID-19 pandemic, many medical activities were suspended. There are few data in the literature evaluating the impact of the pandemic on the evolution of patients with melanoma. OBJECTIVES: This study aimed to evaluate the impact of the COVID-19 pandemic on the epidemiological, clinical and histopathological aspects of melanomas diagnosed at the Instituto de Dermatologia Professor Rubem David Azulay (IDPRDA). METHODS: This is an observational, retrospective and unicentric study, where the requests and histopathological reports of skin biopsies performed at IDPRDA between January 2018 and December 2021 were reviewed and their epidemiological and clinicopathological aspects were subsequently evaluated. RESULTS: A significantly lower incidence of melanoma diagnosis was not found during the pandemic years, but patients were diagnosed at more advanced stages of the disease, which shows a delay in diagnosis due to Covid-19.